Visual vitriol : the street art and subcultures of the punk and hardcore generation - Ensminger, David A. (University Press of Mississippi, 2011)
Visual Vitriol: The Street Art and Subcultures of the Punk and Hardcore Generation is a vibrant, in-depth, and visually appealing history of punk, which reveals punk concert flyers as urban folk art. David Ensminger exposes the movement's deeply participatory street art, including flyers, stencils, and graffiti. This discovery leads him to an examination of the often-overlooked presence of African Americans, Latinos, women, and gays and lesbians who have widely impacted the worldviews and music of this subculture. Then Ensminger, the former editor of fanzine Left of the Dial, looks at how mai.